Increased atmospheric ammonia over the world's major agricultural areas detected from space. Issue 6 (17th March 2017) - Warner, J. X.; Dickerson, R. R.; Wei, Z.; Strow, L. L.; Wang, Y.; Liang, Q.
Abstract: This study provides evidence of substantial increases in atmospheric ammonia (NH3 ) concentrations (14 year) over several of the worlds major agricultural regions, using recently available retrievals from the Atmospheric Infrared Sounder (AIRS) aboard NASA's Aqua satellite. The main sources of atmospheric NH3 are farming and animal husbandry involving reactive nitrogen ultimately derived from fertilizer use; rates of emission are also sensitive to climate change. Significant increasing trends are seen over the U.S. (2.61% yr −1 ), the European Union (EU) (1.83% yr −1 ), and China (2.27% yr −1 ). Over the EU, the trend results from decreased scavenging by acid aerosols. Over the U.S., the increase results from a combination of decreased chemical loss and increased soil temperatures. Over China, decreased chemical loss, increasing temperatures, and increased fertilizer use all play a role. Over South Asia, increased NH3 emissions are masked by increased SO2 and NO x emissions, leading to increased aerosol loading and adverse health effects. Key Points: First decade‐long ammonia records (2002–2016) were retrieved from AIRS satellite daily measurements Substantial increases in ammonia concentrations are observed over several of the world's major agricultural regions Causes of ammonia increase include increased fertilizer use, increasing temperatures, and decreased loss to aerosols